Relaksasi Otot Progresif untuk Mengurangi Gejala Fatigue pada Klien Diabetes Mellitus Tipe 2 di Wilayah Kerja Pusat Kesehatan Masyarakat Kayon - Reny Sulistyowati; Agnes Dewi Astuti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Diabetes mellitus (DM) is a group of heterogeneous disorders characterised by increases in blood glucose levels or hyperglycemia. Symptoms of fatigue are a widespread clinical complaint among adults with type 2 diabetes, this is associated with and reported to be bad for health and is a significant obstacle to the successful management of diabetes. Fluctuations in glucose levels can also cause fatigue. Progressive Muscle Relaxation is one of the natural and simple relaxation techniques. Based on the research that has been done, Progressive Muscle Relaxation can help to reduce fatigue symptoms in Type 2 DM clients. Community service activities were carried out in the PKM Kayon Working Area, precisely at Posbindu Bethesda for 30 participants. The activities include providing health services in the form of blood pressure measurement and blood glucose level examination, providing health education about DM and teaching progressive muscle training. The media used are leaflets and booklets. Participants enthusiastically participated in the activities from the beginning to the end. The evaluation that has been done, the post-test results for knowledge of DM have an increase in the average value of expertise by 17.85%.